Effectiveness of Pop Up Book Media Based on Problem Based Learning in Improving the Problem Solving Abilities of Grade V Elementary School Students - Nafilatun Husna; Susilawati Susilawati; Dewi Yulianawati (Journal of Educational Sciences, 2026)
The research was motivated by the low problem solving skills of elementary students in learning food chain material, which necessitate the use of innovative learning media and models. The novelty of this study lies in the integration of Pop Up Book media and the Problem Based Learning (PBL) model to enhance elementary students’ problem solving skills in food chain learning, while previous studies have generally examined these approaches separately. This study aimed to determine the effect of PBL based Pop Up Book media on the problem solving skills of fifth grade students at SD Negeri 2 Sumber. The study employed a quasi-experimental method with a nonequivalent control group design involving 46 students. Data were analyzed using normality and homogeneity tests, an Independent Samples t-test, and N-Gain analysis. The results showed a significance value of 0.000 < 0.05, indicating a significant effect of the intervention. The experimental class achieved a higher posttest mean score (82.43) than the control class (55.74), with N-Gain scores of 63.75% and 12.10%, respectively. These findings indicate that the intervention had a substantial positive effect on students’ problem-solving skills and can serve as an effective instructional strategy for elementary science learning. Therefore, PBL based Pop Up Book media is effective in improving students’ problem-solving skills.